SOCIAL SIGN SYSTEMS OF THE VISUAL URBAN ENVIRONMENT IN THE CONTEXT OF EAST-WEST CULTURAL DIALOGUE - Чучук, С. М. (Art and Design, 2020)
The purpose of the study is to reveal the characteristic artistic and figurative specifics of the social sign system’s organization patterns of visual spaces of China and Poland in the context of contrasting worldviews, mental, ethnic features of the population. Methodology. Historical method, method of visual observation, method of system-comparative analysis, method of artistic-compositional analysis. Results. The specifics of the social sign system’s organization in the urbanenvironments of China (the case of Xuzhou city) and Poland (the case of Opole city) are analyzed; the influence of worldview, mental and ethnic peculiarities of the populatio on the formation of aesthetic traditions of artistic activity in the public space of cities is assessed; a comparative analysis of the eastern and western artistic and figurative tendencies is carried out; the key focuses of strategies for organizing the visual field of cities are described. Scientific novelty. Cities’ visual space social sign system in the context of the opposition of aesthetic, artistic and figurative tendencies of China and Poland is studied; the socio-cultural preconditions for the formation of Chinese and Polish social sign system’s specific features of are revealed. Practical significance. The results of the research can become a theoretical, factual basis for the development of general and special courses in art history studies, as well as the basis of practical programs for the transformation of modern cities’ visual spaces.